2021
DOI: 10.1001/jamanetworkopen.2021.18824
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Periconceptional Weight of Maternal Grandmothers and Attention-Deficit/Hyperactivity Disorder in Grandchildren

Abstract: IMPORTANCE Neurodevelopmental disorders have been proposed to involve alterations to epigenetic regulation, and epigenetic effects may extend to germline cells to affect later generations.Weight status may affect DNA methylation, and maternal weight before and during pregnancy has been associated with offspring DNA methylation as well as attention-deficit/hyperactivity disorder (ADHD).OBJECTIVE To assess whether a woman's weight before and during pregnancy is associated with ADHD in her grandchild. DESIGN, SET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 97 publications
(161 reference statements)
0
2
0
Order By: Relevance
“…Of the 35 included studies, 24 were prospective studies [ 23 46 ], 6 were retrospective studies [ 47 52 ]and 5 were case–control studies [ 53 57 ] ( Table 1 ). Note that 4 articles included in their analysis two cohorts.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 35 included studies, 24 were prospective studies [ 23 46 ], 6 were retrospective studies [ 47 52 ]and 5 were case–control studies [ 53 57 ] ( Table 1 ). Note that 4 articles included in their analysis two cohorts.…”
Section: Resultsmentioning
confidence: 99%
“…Our results above were similar to a study in Kenya which showed that mothers who were overweight or obese had higher odds of having children who were overweight or obese [ 43 ], as well as research in Finland that found the children who had newly diagnosed type 1 diabetes were influenced by grandparents with type 2 diabetes [ 44 ]. Moreover, a study in the U.S. found that grandmothers who were underweight prior to pregnancy had an increased risk of attention-deficit/hyperactivity disorder among their grandchildren [ 45 ]. The results of this study illustrated that social and community networks (including family and wider social circles), as one part of the ‘social determinants of health’, played an important role in determining the quality of the health of a population [ 46 ].…”
Section: Discussionmentioning
confidence: 99%